Characteristics of physical activity in inhabitants of the Pilsner region during years 2005-2009 - Petr Valach; Jana Vašíčková; Jaromír Votík; Marie Lukavská; Tomáš Klobouk; Jan Dygrýn (Palacký University Olomouc, 2011)
BACKGROUND: The physical activity (PA) of inhabitants from the Pilsner region can be influenced by specific regional characteristics. The overall PA can be influenced by various other factors that are predetermined mainly by social and environmental conditions. AIM: The aim of this study was to identify the level of PA by inhabitants from the Pilsner region. We also analyzed what other personal or environmental factors may influence the amount of overall PA of this population group. METHODS: Inhabitants from the Pilsner region in age of 25-58 years took part in a random selection carried out throughout the research survey in years 2005-2009. Respondents were visited and addressed by students from the West Bohemian University in Pilsen who explained them the matter of survey and gave them questionnaire ANEWS. Students came back for filled questionnaires after one week. We made analysis of the questionnaire, which contains also IPAQ long, and used data concerning amount and type of PA realized throughout one week and also data including information about neighborhood environment. RESULTS: For final analysis we used data from correctly and completely filled questionnaires from 1,125 inhabitants of the Pilsner region (513 men in age of 41.12 ± 9.56 years and 612 women in age of 40.88 ± 8.54 years). We found significant difference in the level of overall PA among particular groups of men only in category "completed education" (p < 0.01; d = 0.32) where elementary educated men performed the highest amount of PA. The most important item manifesting statistically significant difference in women was a dog ownership (p < 0.01; d = 0.30). The biggest differences between men and women were identified by PA at work and vigorous PA in favor of men when the effect size showed small effect. CONCLUSION: The level of overall PA of men from the Pilsner region is from the presented items of the questionnaire ANEWS significantly influenced only by attained elementary education and type of multistorey buildings in neighborhood. At the same time men show higher amount of vigorous PA and higher level of overall PA at work compared to women, whose level of overall PA is significantly influenced only by a dog ownership.